Optimalisasi Pertumbuhan Benih Ikan Dewa (Tor soro) melalui Kombinasi Tepung Lemna perpusilla dan Pakan Komersial - Cindi N Manurung; Yulisman Yulisman; Dade Jubaedah; Ferdinand Hukama Taqwa; Muslim Muslim; Revita Syefti Palmi (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2026)
The Mahseer (Tor soro), an omnivore with herbivorous tendencies, requires a balanced combination of plant and animal-based nutrients. Lemna perpusilla shows high potential as a cost-effective, plant-based feed ingredient. This study aimed to determine the optimum combination of L. perpusilla meal and commercial feed to maximize the growth performance of T. soro. A completely randomized design (CRD) was employed with five treatments and three replications: P0 (100% L. perpusilla), P1 (75% L. perpusilla + 25% commercial feed), P2 (50% L. perpusilla + 50% commercial feed), P3 (25% L. perpusilla + 75% commercial feed), and P4 (100% commercial feed). The results revealed that P3 was the optimal formulation, showing the highest growth rates, protein efficiency ratio, and feed conversion ratio as follows: absolute weight growth of 0.66 ± 0.14 g, absolute length growth of 0.73 ± 0.06 cm, a protein efficiency ratio (PER) of 2.71 ± 0.65, a feed conversion ratio (FCR) of 1.24 ± 0.28, and a 100% survival rate. Water quality parameters remained within the tolerable range for T. soro culture. In conclusion, incorporating 25% L. perpusilla meal into commercial feed significantly supports growth performance, providing a clear and effective strategy for sustainable T. soro culture.